Prevalence and impact of rapid eye movement sleep behavior disorder in multiple system atrophy: a systematic review and meta-analysis - Wang, Hui; Zhang, Ting; Fan, Wenhui (Frontiers in Neurology, 2024)
Objective Multiple system atrophy (MSA) is commonly associated with rapid eye movement sleep behavior disorder (RBD). Research on the prevalence of RBD in MSA and its effects on MSA patients has yielded inconsistent results. Currently, there is only one meta-analysis discussing the prevalence of RBD in MSA, but no meta-analysis discussing the impact of RBD on MSA. Methods A systematic review and meta-analysis was conducted by searching studies related to MSA and RBD in PubMed, Web of Science, Embase, and Cochrane databases. Data were pooled as necessary to calculate prevalence of RBD, odds ratio (OR), weighted mean differences (WMD) with 95% confidence intervals (CI). Heterogeneity was assessed using the I2 statistic. Results The prevalence of polysomnography confirmed-RBD in MSA was 79.9% (95% CI, 68.8–89.3%) in a pooled sample of 598 subjects. Patients with MSA who had RBD were notably younger at examination than those without RBD (WMD −3.26 years, 95% CI −4.99 to −1.53), and the age of disease onset in MSA patients with RBD was significantly lower than in those without RBD (WMD −3.27, 95% CI −5.06 to −1.48). Additionally, RBD was more common among male patients with MSA compared to female patients (OR 2.11, 95% CI 1.31 to 3.39). MSA patients with RBD also exhibited significantly higher Unified Multiple System Atrophy Rating Scale (UMSARS) I and IV scores than those without RBD (WMD 2.99, 95% CI 0.10 to 4.88, and WMD 0.23, 95% CI 0.03 to 0.43). Conclusion The prevalence of polysomnography-confirmed RBD in MSA is 79.9%. The prevalence in Asian population was lower than in Europe and America, which might be related to an underestimation in Asian populations. Additionally, patients with MSA and RBD tend to be younger at examination, have an earlier age of onset, and exhibit more severe disease manifestations compared to MSA patients without RBD.